Short Communication: Kajian Etik, Kesejahteraan, dan Kesehatan Hewan dalam Fenomena Topeng Monyet - Erie Kolya Nasution (Yayasan Literasi Sains Indonesia, 2022)
The phenomenon of dancing monkeys is a cultural and traditional art in Indonesia by exploiting primates, especially the Macaca fascicularis or long-tailed macaque species. Law enforcement efforts related to the dancing monkey phenomenon seem biased. Apart from the fact that the long-tailed macaque is one of the unprotected animals, there is also no strict enforcement of existing laws, although they can often be charged with animal health and welfare regulations. This study discusses the urgency of ethics, animal welfare, and health in primates who used dancing monkeys as objects. The method used is a descriptive-qualitative approach based on the relevant scientific literature. There is still very little research related to the dancing monkey phenomenon, both in terms of ethics, animal welfare, and health, the urgency and further recommendations from the results of this study can be used to encourage efforts to prevent the dancing monkey phenomenon in the community by providing suggestions that can be applied to the community such as education, development of informative media, management of educative tourism objects based on wildlife and ecotourism, and participating in volunteering for animal observers or animal welfare in Indonesia.